Does genetic polymorphisms affect health? - Ismail, Patimah (Universiti Putra Malaysia Press, 2011)
Genetic polymorphisms are variations found in DNA sequences and they are integral to the development of genetic markers to identify individuals at risk and it requires certain techniques and strategies to detect the mutations. Most of the variations found in DNA sequences are stable and occur in the form of single nucleotide polymorphism (SNPs),insertion/deletion (I/D) and variable tandem repeats. Among the genetic polymorphisms, SNPs are the most abundant form in the human genome, accounting for more than 90% of all differences among individuals. Variation occurs when a single nucleotide (A, T, C, or G) alters in the genome sequence. SNPs are stable, di-allelic and the two alleles represent the “wild-type” and the “mutant type” forms. SNPs are frequently studied in relation to various cancers for their known biochemical or physiological function. Several studies have been done in understanding the possible role of genetic variation in the human genome. Identifying the association between the ancestral variants in genes are common in polygenic diseases which become increasingly reasonable with improved methods for detecting genetic variants on a genome-wide scale. Over the years, several researches have been conducted to detect the cause of various genetic disorders. Genetic polymorphisms play an important role in human health especially in the development of essential hypertension and type 2 diabetes mellitus. Our genetic research group works toward understanding the interaction between genes and environmental exposures in various human diseases such as congenital heart disease, hypertension, metabolic syndrome, end stage renal disease, prostate cancer, polycystic kidney disease etc. Our group research has two main elements: investigating the role of environmental exposure in critical target gene mutation and the role of genetic susceptibility and environmental exposure in those disorders. In addition, more fundamental researches are going on in order to know the genetic and allelic frequency of certain susceptibility genes for the development of various disorders